"I Can Defend Myself": Women's Strategies for Coping With Harassment While Gaming Online. (March 2017) - Cote, Amanda C.
Although video game audiences have greatly diversified over recent years, players who are not the stereotypical straight, White, male "gamer" are still frequently viewed as outsiders to online gaming and face harassment because of this status. However, many choose to play games despite this and have developed specific coping strategies they employ to avoid or respond to harassment. Using grounded theory and in-depth interviews with female gamers, this gender-based case study explores women's strategies for coping with online game-related harassment. It shows that women are first and foremost an active audience, carefully managing their media environment to help ensure positive experiences. At the same time, their strategies come with limitations, such as hiding their contributions to gaming or provoking further harassment. Although women are capable media managers, their continued status as "outsiders" deeply affects their gaming experiences and demonstrates a need for cultural change in online environments.